PENGAPLIKASIAN TEORI HERMENEUTIKA HANS-GEORG GADAMER TERHADAP HADIS NABI MUHAMMAD - MUH. ILHAM R. KURNIAWAN (IAIN Kediri, 2021)
AbstractThe hadiths of the Prophet are present in people's lives today in a 'frozen' form and have no application. This has prompted the initiation of various breakthroughs to find a way out of the coldness for the 'native' hadith to conform to the demands of the times. One of them is through the hermeneutic approach in the interpretation of hadith. The hermeneutic approach in the interpretation of hadith can be taken through three layers of interpretation, namely: 1. Interpretation